Evidence of resilience to past climate change in Southwest Asia: Early farming communities and the 9.2 and 8.2 ka events. (15th March 2016) - Flohr, Pascal; Fleitmann, Dominik; Matthews, Roger; Matthews, Wendy; Black, Stuart
Abstract: Climate change is often cited as a major factor in social change. The so-called 8.2 ka event was one of the most pronounced and abrupt Holocene cold and arid events. The 9.2 ka event was similar, albeit of a smaller magnitude. Both events affected the Northern Hemisphere climate and caused cooling and aridification in Southwest Asia. Yet, the impacts of the 8.2 and 9.2 ka events on early farming communities in this region are not well understood. Current hypotheses for an effect of the 8.2 ka event vary from large-scale site abandonment and migration (including the Neolithisation of Europe) to continuation of occupation and local adaptation, while impacts of the 9.2 ka have not previously been systematically studied. In this paper, we present a thorough assessment of available, quality-checked radiocarbon ( 14 C) dates for sites from Southwest Asia covering the time interval between 9500 and 7500 cal BP, which we interpret in combination with archaeological evidence. In this way, the synchronicity between changes observed in the archaeological record and the rapid climate events is tested. It is shown that there is no evidence for a simultaneous and widespread collapse, large-scale site abandonment, or migration at the time of the events. However, there are indications for local adaptation. We conclude that early farming communities were resilient to the abrupt, severe climate changes at 9250 and 8200 cal BP. Highlights: We assess the impacts of the 9.2 and 8.2 ka BP climate events on Southwest Asian farming communities. We use over 3000 quality-checked 14 C-dates in combination with archaeological evidence. No large-scale collapse/decline or migration took place at around 9250 or 8200 cal BP. There is some evidence for local adaptation, but not at all sites. Early farming communities in Southwest Asia were resilient to rapid climate change.